Stereo-controlled approach to pyrrolidine iminosugar C-glycosides and 1,4-dideoxy-1,4-imino-L-allitol using a D-mannose-derived cyclic nitrone - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D.; Lombardo, Marco (Tetrahedron Letters, 2009)
Intramolecular N-alkylation of 2,3-O-isopropylidene-5-O-methanesulfonyl-6-O-t-butyldimethylsilyl-D-mann ofuranose-oxime 7 afforded a five-membered cyclic nitrone 9, which on N-O bond reductive cleavage followed by deprotection of -OTBS and acetonide functionalities gave 1,4-dideoxy-1,4-imino-L-allitol (DIA) 3. Addition of allylmagnesium chloride to nitrone 9 afforded alpha-allylated product 10a in high diastereoselectivity providing an easy entry to N-hydroxy-C1-alpha-allyl-substituted pyrrolidine iminosugar 4a after removal of protecting group, while N-O bond reductive cleavage in 10a afforded C1-alpha-allyl-pyrrolidine iminosugar 4b. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cyclic nitrone; Enzyme inhibitors; Iminosugars; pyrrolidine

Synthesis and conformational study of chiral oxepines: the baylis-hillman reaction and RCM approach with sugar aldehyde - Jadhav, Vrushali H.; Bande, Omprakash P.; Pinjari, Rahul V.; Gejji, Shridhar P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2009)
The Baylis-Hillman reaction of 3-O-allyl-alpha-D-xylo-pentodialdo-1,4-furanose 3 afforded a diastereomeric mixture of D-gluco- and L-ido-configured alpha-methylene-beta-hydroxy esters 4a and 4b, respectively, in a ratio of 2:3. Reduction of the ester functionality in 4a/4b gave alcohols 5a/5b. The diene thus formed in 5a/5b was subjected to ring-closing metathesis (Grubbs' second-generation catalyst) to afford oxa-bicyclic ring system 6a/6b in high yield. Further manipulation of the aectonide functionality in 6a and 6b afforded new polyhydroxylated oxepines 1a/2a and 1b/2b, respectively. The (1)H NMR of oxepines 1a and 1b in D(2)O showed doubling of signals indicating their existence in two different rotamers/conformers. This fact was substantiated by calculating energetics of 1 and 2 conformers using the density functional theory and correlating the calculated (1)H NMR chemical shift pattern with that of the experimental spectra.

Synthesis of azepane and nojirimycin iminosugars: the sharpless asymmetric epoxidation of D-glucose-derived allyl alcohol and highly regioselective epoxide ring opening using sodium azide - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron-Asymmetry, 2010)
The Sharp less asymmetric epoxidation of D-glucose-derived ally! alcohol 4 afforded alpha- and beta-epoxides 5a and 5b in high stereoselectivity. The epoxide ring opening in 5a/5b was studied with different nucleophilic azido reagents, under various reaction conditions, and was found to be highly regioselective to give the preferential formation of 6-azido diol 6a/6b over 5-azido-diol 7a/7b. The 6-azido diol 6a/6b and 5-azido dial 7a/7b thus obtained were converted to the corresponding seven- and six-membered iminosugar, namely, azepane 1a/1b and 1-deoxy-nojirimycin 2a/2b. (C) 2010 Elsevier Ltd. All rights reserved.

Synthesis of eight-membered iminocyclitols from D-glucose - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2010)
The Baylis-Hillman reaction of 3-o-benzyl-alpha-d-xylo-pentodialdo-1,4-furanose 2 afforded a diastereomeric mixture of L-ido- and D-gluco-configurated alpha-methylene-beta-hydroxy esters 3a and 3b, respectively, in 1:1 ratio. Conjugate addition of benzyl amine on 3a gave adduct 4a as a major product while, addition of benzyl amine to 3b gave only one diastereomer 4b. Reduction of ester functionality in 4a/4b, opening of 1,2-acetonide functionality followed by reductive amino-cyclization under hydrogenation condition afforded azocanes 1c/1d in good yield. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Baylis-Hillman reaction; Conjugate addition; diastereoselectivity; Iminosugars

Synthesis of (+/-) debenzoyl analogs of norsampsones as potential anticancer agents - Jadhav, Amol R.; Thombal, Raju S.; Nigam, Preeti; Jadhav, Vrushali H. (Tetrahedron Letters, 2015)
Synthesis of (+/-) debenzoyl analogs of norsampsones 1 and 2 is reported starting from commercially available 1,3-cyclohexadione in six steps with overall yields of 37% and 36%, respectively. Compounds 1 and 2 were tested for their anticancer activity and showed moderate anticancer activity against HeLa cell lines. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Acylphloroglucinols; Anticancer; Debenzoyl; Norsampsones

Sulfonated graphene oxide as highly efficient catalyst for glycosylation - Thombal, Raju S.; Jadhav, Vrushali H. (Journal of Carbohydrate Chemistry, 2016)
Heterogeneous sulfonated graphene oxide for the first time has been used as a green and efficient catalyst for atom-economic glycosylation of unprotected, unactivated glycosyl donors or 2,3,4,6-tetra-O-acetylglycosyltrichloroacetimidate with various acceptors basically in the absence of solvent. The unprotected, unactivated glycosyl donors afforded mixtures of alpha- and beta-glycosides, while the 2,3,4,6-tetra-O-acetylglycosyltrichloroacetimidate afforded beta-glycosylated products with high yields and selectivity. The main advantages of this methodology are easy catalyst preparation, no need for dry reagents and reaction conditions, easy catalyst separation and recycling, and high product yields.
Keywords: glycol donor; glycosyl acceptor; glycosylation; reusability; Sulfonated graphene oxide

Selective oxidation of biomass derived 5-hydroxymethylfurfural (HMF) to 2,5-diformylfuran (DFF) over spent dry cell battery cathode material (BCM-2) - Ghadge, Sambhaji S.; Bankar, Shubham R.; Jadhav, Vrushali H. (ACS Applied Engineering Materials, 2024)
Widespread use of batteries across the globe generates a huge amount of waste. This work is the first to report spent dry cell (Zn-Carbon) battery cathode material (BCM-2) as a heterogeneous catalyst for selective synthesis of fine chemical 2,5-diformylfuran (DFF). Cathode material was easily separated from spent batteries, and acid leached followed by calcination to obtain black powder that was denoted as BCM-2. The catalyst was characterized using various techniques such as P-XRD, EDAX, SEM, HR-TEM, TGA, XPS, and BET analysis. Superior catalytic activity was shown by the catalyst for selective formation of DFF using molecular O2 as a sole oxidant. The catalyst was found to give excellent HMF conversion of 97% with 98% high selectivity of DFF. The BCM-2 catalyst was easily recycled and reused without any significant loss in its catalytic activity. This is one of the best examples for a sustainable, cost-effective, and highly efficient catalytic system for the synthesis of the value-added chemical DFF.